The intervention of the judicial system in order to maximise the prevention of chemical risk in operating theatres and to put personal health and safety first - Oddo, Antonio (La Medicina del Lavoro, 2016)
This new paper on chemical risk from anaesthetic agents in operating theatres is the natural progression of that published in this journal in supplement 1-2013, as it constitutes a development and complement of the previous work and an applicative confirmation from the highest organ of administrative justice, the Consiglio di Stato, regarding, in particular, the obligation of adopting the technically most advanced “measures” to eliminate or, at least, minimise risk in the use of new generation and the most commonly-used anaesthetic agents (sevoflurane and desflurane).  Therefore, in this paper, the authors commence by referring to the starting point, consisting in the conclusions of the previous study, which highlighted the extraordinary convergence of technical and scientific, legislative and case law data on the same result, constituted by the possibility, and consequent obligation, of implementing, also in operating theatres, the greatest technologically possible safety, starting with the choice of the most suitable equipment, methods and quality systems for avoiding the diffusion, dispersion and /or leakage of volatile hazardous agents that may contribute - together with those chemical reactions that are foreseeable and avoidable, given the characteristics of the materials, substances and relative “packaging” - to workplace pollution, which can, in any case, reach levels that are hazardous due to the concentration of anaesthetic gases. Subsequently, once the “scientific” fruit of the previous contributions has been discussed, the authors evaluate the impact of the result already achieved in practice with concrete cases and the judgement expressed with a series of judgements issued in rapid succession by the Consiglio di Stato, showing the application, not merely of the legislative “data” but also of the references and citations that these “data” contain regarding the “knowledge acquired regarding the relationship with technical progress”. Lastly, the Authors provide, as a further, definitive conclusion, the singular unit of the guidelines provided by case law, the result of a univocal and continuous multitude of judgements issued at the highest degree of administrative justice, albeit for very diverse situations and circumstances, which provide, therefore, a direction and an operative guide for which they are called on to adopt roles and responsibilities for the choices of “products”, “systems” and “methods” destined to affect - for the use of anaesthetic agents - the health and safety of healthcare staff and of patients themselves.